Natural and Anthropogenic Sources Controlling Regional Groundwater Geochemistry on the Niagara Peninsula - Smal, Caitlin (My University, 2017)
Groundwater chemistry on the Niagara Peninsula has been identified as highly mineralized in comparison to groundwaters collected from the same bedrock formations elsewhere in southern Ontario. Three geochemical zones were discerned using hierarchical cluster analysis and other geochemical and isotopic methods. The Escarpment Zone, located along the Niagara and Onondaga Escarpments, is characterized by unconfined aquifer conditions, parameters reflective of surficial contaminants, including road salt, and elevated HCO3, DOC, NO3-, coliform bacteria and tritium. In contrast, in the Salina Zone thick, low-permeability sediments and gypsiferous bedrock results in highly mineralized groundwaters with Ca-SO4 geochemical facies and elevated S2-, Ca2+, Mg2+, K+, Na+, SO42-, Cl-, Br-, Sr2+, NH4+ and CH4. The Guelph Zone contains the lowest electrical conductivity of the three zones and elevated F-. Outliers exist with groundwater geochemistry that differs from the local geochemical zone and the host aquifer. These sites have elevated SO42- (>1000 to 5200 mg/L) with depleted δ34SSO4 (-2.2 to 14.3‰ VCDT) signatures that differs starkly from Devonian and Silurian evaporites (~20 to 32 ‰) in the host formations. This exogenic SO4 was identified in a cross-formational northeast – southwest linear trend crossing three major groundwater flow systems. The lack of down-stream impact in these systems and tritium groundwater ages that are typically only decades old indicate a young, non-geological origin and implicate anthropogenic activities. Additionally, nine samples were identified with elevated methane concentrations and δ13CCH4 signatures within the thermogenic range. As thermogenic methane is not produced within shallow aquifers and would be short-lived in the presence of the ubiquitous sulfate, these samples imply recent upward migration of methane from depth through vertical conduits. Taken together, the evidence supports large-scale upward movement of fluids in the centre of the Niagara geochemical anomaly and more sporadic upward transport of gases over a wider area of the peninsula. The most likely vector is through corroded and leaking casings or boreholes of abandoned (century) gas wells that are common across the peninsula.
Keywords: geochemistry, hydrogeology, Niagara Peninsula, Niagara, stable isotopes, carbon isotopes, sulfur isotopes, tritium, water isotopes, ABB, Appalachian Basin Brines, southern Ontario, gas wells, hierarchical cluster analysis, HCA, groundwater evolution, thermogenic methane, biogenic methane, sulfate, evaporite dissolution, anthropogenic, road salt, karst, carbonate dissolution, bedrock aquifers, sediment thickness, Salina, Niagara Escarpment, Onondaga Escarpment, hydrogeochemistry